Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Verna Lalbeharie joins EdTech Hub as incoming Executive Director - Hub, EdTech (EdTech Hub, 2021)
We are excited to announce that Verna Lalbeharie is joining EdTech Hub as the incoming Executive Director. A native of South Africa, now living in North Carolina (USA), Lalbeharie brings not only 25 years of EdTech expertise to the role, but also a career-spanning commitment to evidence-building in education technology to create a more equitable future for all students. “When…
Keywords: _EdTechHub_Output

Highlights from EdTech and Covid-19: Lessons learned, future plans - Team, EdTech Hub (EdTech Hub, 2021)
On March 2nd EdTech Hub brought together education leaders, including teachers, program managers and policymakers, to reflect on a year of EdTech and Covid-19, discuss the lessons learned so far and consider how we can prepare for the future.  Over 200 people joined from around the world for a lively and thought-provoking discussion. Speakers included:  Helen Grant MP, UK Prime…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessey, Sarah; Jordan, Katy; Wagner, Daniel; EdTech Hub Team (EdTech Hub, 2021)
Keywords: ⛔ No INSPIRE recid found

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Advancing evidence-based decision making in LMICs: Focus of EdTech Hub’s work - Hennessy, Sara (EdTech Hub, 2021)
This blog sets out the Hub’s aims and approaches to identifying appropriate and effective uses of EdTech that can potentially raise learning outcomes in low- and middle-income countries (LMICs). Research shows that EdTech offers immense potential, but sustainable and positive change at scale has largely proved elusive in practice – particularly for marginalised learners where we focus our work.  To…
Keywords: _EdTechHub_Output

What we learnt in the Sandbox between onebillion, VSO Malawi and EdTech Hub (Sprint Review Draft) - Dinham, Nat; Plaut, Daniel; Rahman, Asad; Schmit, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _comingsoon; _r:AddedByZotZen

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Determining the suitability of Whatsapp for Jusoor Azima Project - Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Social And Emotional Learning and EdTech: An Evidence Review - Kalifa, Damani (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _r:AddedByZotZen

WhatsApp-Assisted Learning for Refugees. End of Sandbox Sprint 3 - Boujikian, Michèle; Carter, Alice; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

A Case for a Systems Approach to EdTech - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech for Learners with Disabilities in Primary School Settings in LMICS: A Systematic Literature Review - Lynch, Paul; Singhal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
This systematic literature review was guided by the overarching aim of establishing the categories of EdTech that may be appropriate to support the learning of children with disabilities aged 4–12 years in low-and middle-income countries. A critical review of the published literature was deemed essential as the field of disability and EdTech (mirroring larger trends in disability and educational research) has remained dominated by anecdotal commentaries and strong personal assertions, but substantiated by little evidence. In framing the review we drew on a dual model of access which provides a helpful lens into how EdTech can support a learner’s development trajectory across different interventions (e.g. learning to read Braille or sign language), targeted educational outcomes, inclusive practices and suitable accommodations in different educational settings. This approach is underpinned by a human rights agenda, as articulated in the UN Convention for the Rights of Persons with Disabilities (CRPD) and the Sustainable Development Goals (SDGs) which demand fair and equal access to education for all children and young people. They are also concerned, though, that an individual child/young person should have agency, self-determination and independence. Article 2 of the CRPD unambiguously recognizes that reasonable accommodation is vital in enabling persons with disabilities to enjoy and exercise their rights on an equal basis with others.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTechTools Relaunched with TVET Resources - EdTech Hub; Generation Unlimited (EdTech Hub, 2021)
EdTechHub, Generation Unlimited (GenU), UNESCO and UNESCO-UNEVOC have joined forces to relaunch EdTechTools (formerly the Tools Database): a global repository of education technology tools and platforms designed to help decision makers at all levels in the global education and training community find resources that facilitate and support remote learning. More than a year after the world experienced an education disruption…
Keywords: _EdTechHub_Output

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

EdTech and Covid-19: the story so far - Gould, Briony (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Embracing EdTech: four critical questions answered through a rapid prototype programme on teachers’ professional development (TPD) - Sabbab, Salman; Shakil, Abdullah All; Alam, Faria (EdTech Hub, 2021)
Seventy-one teachers participating in the ‘Onneshon’ prototype were flooding the WhatsApp group with messages about the challenges and hiccups they were experiencing, either with watching the video content or with taking a quiz in the first two weeks. Problems were pouring in and so were solutions being innovated and offered through diverse channels. In the space of two weeks, the…
Keywords: _EdTechHub_Output

EdTech and Covid-19: lessons from around the world - Pellini, Arnaldo (EdTech Hub, 2021)
Arnaldo Pellini, Susan Nicolai, Moizza Binat Sarwar, Sam Wilson, Akanksha Bapna, Chris McBurnie, Adedoyin Adesina, Oladele Akogun, Ernest Ngabo, Hind Al-Hindawi, Ni Wayan Suriastini, Vollan Ochieng, Moses Ngware, Asma Rabi , Abdul Musawir, Clement Sefa-Nyarko, Edem Agbe , Rabia Tabassum, Amna Zaidi, Jeroen Groenewegen, Harish Doraiswamy, Sudhansu Sharma, Liangdi Xu In this blog we summarise four takeaways from a reflection…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for learners with disabilities: urgent need to focus on access, engagement and learning outcomes - Singal, Nidhi; Lynch, Paul; Kaye, Tom; Francis, Gill (EdTech Hub, 2021)
The current approaches to providing high quality learning experiences to learners with disabilities in low and middle-income (LMICs) countries requires radical rethinking. To date, significant numbers of learners with disabilities are not enjoying the benefits of barrier-free and meaningful engagement with the school curriculum in order to reach their potential. Appropriately matched technology to learner needs – in terms of…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Hello and Welcome to the Sandbox - Simpson, Lea; Carter, Alice; Rahman, Asad (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _r:AddedByZotZen

The Use of Technology in the CPD Implementation Plan in Tanzania - Adam, Taskeen; El-Sefary, Yomna; Haßler, Björn; Khalayleh, Abdullah; Kremeia, Adam; Proctor, Jamie; Mtebe, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Introducing: A political economy framework for EdTech evidence uptake - Pellini, Arnaldo; Nicolai, Susan; Kreimeia, Adam; Wilson, Sam (EdTech Hub, 2021)
“Without context, words and actions have no meaning at all”  – Gregory Bateson Evidence only makes a difference if it is used. While the EdTech field suffers from significant gaps in knowledge, more research won’t mean much unless it can be used to inform policy and decision-making. And to do this, an understanding of the context and of how individuals…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Sierra Leone series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health. - Tahi (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.   In week one, we connected with Abdulai Swaray and Bai Kamara from the Pikin-to-Pikin Movement.…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Helping improve the Kenya Education Cloud with a SWOT analysis - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
In early 2021, EdTech Hub partnered with the Kenya Institute of Curriculum Development to support them to analyse the strengths, weaknesses, opportunities and threats of the Kenya Education Cloud. This blog highlights what we learnt, and lessons that can inform the development of Virtual Learning Environments around the world.  Governments all over the world responded to Covid-19 school closures by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using innovative methods to train teachers of blind children: what we learned - Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Governments all over the world have closed learning institutions because of the Covid-19 pandemic, including in Kenya. This has exacerbated the global learning crisis and made it more difficult for teachers, parents, and caregivers to include children with disabilities in quality education. To ensure learners with disabilities were not left behind during Covid-19 school closures, eKitabu partnered with EdTech Hub…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Social Emotional Learning and EdTech: Resources, Examples, and Effective Practices - Rui, Yang (Tingting) (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - Haßler, Björn; Castillejo, Alice; Marzotto, Mia; El-Serafy, Yomna; Khalayleh, Abdullah; Koomar, Saalim; Langa, Ancha; Nyilinkindi, Jacques; Saadeddin, Zeina; Tegha, Ghislaine; Villavicencio Peralta, Xuzel Ana (EdTech Hub, 2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Using evidence to strengthen tech-supported teacher professional development in Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _r:AddedByZotZen; _zenodoETH

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Digital Personalised Learning to Improve Numeracy Outcomes in Kenyan Primary School Classrooms - EdTech Hub (EdTech Hub, 2021)

The Impact of a Tech-Supported, School-Based TCPD Model on Learning Outcomes in Tanzania - EdTech Hub (EdTech Hub, 2021)

Optimising Messaging to Promote Returns to School in Ghana for Marginalised Learners - EdTech Hub (EdTech Hub, 2021)

Low-Tech Personalised Learning to Improve Girls' Education in Kenya - EdTech Hub (EdTech Hub, 2021)

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Research - EdTech Hub (EdTech Hub, 2021)

EdTech and Equity: Position Paper - Zubairi, Asma; Jefferies, Kate; Kreimeia, Adam (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Raising readers: Kenya schools use of technology to improve parent and carers' engagement in literacy learning: Inception Report - Nicolai, Susan; Zubairi, Asma; Bapna, Akanksha; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

Mother Language Day 2021: Improving data on mother-tongue languages for better learning outcomes - EdTech Hub (2021)
To celebrate International Mother Language Day 2021, EdTech Hub’s Björn Haßler spoke with Alice Castillejo and Mia Marzotto of Translators without Borders. They talked about the importance of mother tongue-based education and the need to support speakers of marginalised languages. This blog post captures their conversation. “How do we know that speakers of marginalised languages are left behind?” Alice: Research…

Mapping the education data ecosystem in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

The global stakes of digitalization in education - Haßler, Björn (The global stakes of digitalization in education (Uganda), 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _zenodo:submitted

LGA Implementation Guide for Teacher Continuous Professional Development - Tanzania Institute of Education; Ministry of Education, Science & Technology; President’s Office — Regional and Local Governance (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

test - jac, nyili (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Guidebook to Successful Implementation of Digital Education - Traore, Moussa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Consultants needed for UNESCO ACCRA's review of ICT in Education Policy in Ghana - Tahi (EdTech Hub, 2021)
ICT Transforming Education in Africa: Review of ICT in Education Policy in Ghana  TERMS OF REFERENCE (TOR) FOR INDIVIDUAL CONSULTANTS 1. Background/Context  UNESCO Korean Funds-In-Trust ICT Transforming Education in Africa is a project developed under  the UNESCO-Korea Funds-in-Trust framework to support a selected number of Sub-Saharan  African countries to test scalable and effective models of using information and  communication technologies…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How Bangladesh repurposed pre-existing online platforms to reimagine education during Covid-19 - Bangladesh), Anir Choudhury (a2i (EdTech Hub, 2021)
Forty-two million. That is the total number of students in Bangladesh. Forty-two million potential leaders of tomorrow. Forty-two million reasons to be hopeful for the country’s future. Forty-two million students who, because of Covid-19, were left without classrooms, without their friends, without their schools and colleges – without formal education.
Keywords: _EdTechHub_Output

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

L'utilisation des preuves pour renforcer la formation pédagogique à travers les technologies à Madagascar - Koomar, Saalim; Moss Coflan, Caitlin; Rasolohéry, Hasiniavo (2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodoETH

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Strategy for Tanzania — Focus Area: TCPD in primary schools - El-Serafy, Yomna; Khalayleh, Abdullah; Carter, Alice; Haßler, Björn; Proctor, Jamie; Adam, Taskeen (EdTech Hub, 2021)
Keywords: _EdTechHub_Output

A mixed-methods evidence assessment for emergent fields of knowledge - Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _yl:m

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)

Developing a teacher-focused theory of change for technology-enhanced teaching and learning - EdTech Hub Team (2021)
Internal Brief

17 EdTech Frameworks and Who Needs to Know Them - Bapna, Akanksha; Nicolai, Susan; Myers, Christina; Pellini, Arnaldo; Sharma, Namrata; Wilson, Sam; Wilson, Akanksha Bapna, Susan Nicolai, Christina Myers, Arnaldo Pellini, Namrata Sharma and Sam (EdTech Hub, 2021)
17 EdTech frameworks that provide a valuable bridge between theory and practice. EdTech resources for policy-makers, educational institutions, teachers and multi-stakeholders.

Focus country: Bangladesh - EdTech Hub (2021)

Reimagining Education for Continuous Learning and Teaching - Sengeh, Hon Minister David Moinina; Team, MBSSE Delivery; Team, Hon Minister David Moinina Sengeh and MBSSE Delivery (EdTech Hub, 2021)
EdTech Hub has partnered with the Ministry of Basic and Senior Secondary Education in Sierra Leone to increase the use of evidence in decisions around EdTech. Click to read more.

Digital Learning Solutions | Digital Learning For Every Child - Giraldo, Juan Pablo; Tungatarova, Auken; Cooper, Rachel (EdTech Hub, 2021)
UNICEF and EdTech Hub are partnering together to improve learning outcomes through effective uses of EdTech and digital learning. Read this guest post from UNICEF team members which focuses on the first pillar of UNICEF’s Reimagine Education initiative, world-class digital learning solutions.

Designing and monitoring distance teaching and learning interventions: A guide for projects and implementers - Girls' Education Challenge; Fund Manager; EdTech Hub (2021)

Bibliography on teacher distribution and allocation - Haßler, Björn (2021)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; dode_eth-src-eth

All Programmes Recorded, All Outputs Reported - Haßler, Björn; Adam, Taskeen; Blower, Thomas; El-Serafy, Yomna; Kaye, Tom; Khalayleh, Abdullah; McBurnie, Chris; Megha-Bongnkar, Ghislaine; Regis, Callista (EdTech Hub, 2021)
Keywords: AuthorFirst:Haßler; _yl:q

Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs - McIntyre, Nora; Sabates, Ricardo; Jamieson Eberhardt, Molly (EdTech Hub, 2021)

Keeping Kenya Learning: The importance of caregiver engagement in supporting learning beyond the classroom - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Since the Covid-19 pandemic began, parents, teachers, students and policymakers have been exploring how to support students to learn at home. The emphasis on education at home has made evident the need to better equip caregivers to support their children’s learning.  The Keep Kenya Learning (KKL) initiative is helping parents and caregivers build their capacity and confidence to support learning…
Keywords: _EdTechHub_Output

GIS for Education Working Group - the Education Commission (the Education Commission, 2021)
Keywords: _yl:a

SWOT Analysis of the Kenya Education Cloud - Groeneveld, Caspar; Kimenyi, Eric; Kaye, Tom (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _cover:v3; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Five ways geospatial analysis can help visualize and solve some of education’s biggest challenges - the Education Commission (the Education Commission, 2021)
As the education community continues to mobilize efforts towards achieving Sustainable Development Goal 4 (SDG 4), stakeholders at all levels of the system are grappling with questions on how to deliver inclusive quality education. What communities will benefit most...
Keywords: _yl:c

GIS for Education Working Group launches to promote data-driven decision-making - the Education Commission (the Education Commission, 2021)
Around the world, individuals are using maps to power everyday decisions: how do I navigate from my home to the nearest hospital? How many supermarkets are in my community? What public transportation is available for me to take to work?
Keywords: _yl:b

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

The Storytelling Project Handbook - Dixon, Miranda; Patuck, Lil (EdTech Hub, 2021)

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Innovative Methods to Train Teachers of Blind Children - Kibet, Amon; Kweyu, Ignatius; Koszorus, Ferenc (EdTech Hub, 2021)
Discover what we learned using innovative methods such as virtual training via WhatAapp to train teachers of blind children. Click to read more.

The Importance of Caregiver Engagement in Supporting Learning - Kimathi, Deborah; El-Serafy, Yomna; Plaut, Daniel; Kaye, Tom (EdTech Hub, 2021)
Do you know the importance of caregiver engagement in supporting learning beyond the classroom? Visit our website to learn more.

Scaling Personalised Learning Technology in Malawi - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.

Evidence to Strengthen Tech-Supported Teacher Development in Madagascar - Coflan, Caitlin Moss; Koomar, Saalim; Rasolohery, Hasiniavo (EdTech Hub, 2021)
Our latest blog looks at using evidence to strengthen tech-supported teacher professional development in Madagascar. For more details, visit our website.

Scaling Personalised Learning Technology in Malawi: Lessons from our sandbox with onebillion - Schmitt, Laurel (EdTech Hub, 2021)
Want to know more about the lessons we learnt from our sandbox with onebillion? Read our blog, Scaling personalized learning technology in Malawi.

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)

Turning to technology: A global survey of teachers' responses to the Covid-19 pandemic - Pota, Vikas; Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam; Zubairi, Asma; Aerts, Carla; Gault, Claire (T4 Education & EdTech Hub, 2021)
A global survey of teachers’ responses to the Covid-19 pandemic

CPD Implementation Roadmap - Cambridge Education (Cambridge Education, 2021)